Puzzle: Passing Through ; Signature Collection; Series II - MasterPieces, Inc. (MasterPieces, Inc. Oro Valley, AZ)
1,000 piece puzzle - Passing Through - Upstate New York nostalgic village by lake. Hot air balloons and sailboats in nearby lake.